2021
DOI: 10.1038/s41467-021-23232-7
|View full text |Cite
|
Sign up to set email alerts
|

Polymer-free corticosteroid dimer implants for controlled and sustained drug delivery

Abstract: Polymeric drug carriers are widely used for providing temporal and/or spatial control of drug delivery, with corticosteroids being one class of drugs that have benefitted from their use for the treatment of inflammatory-mediated conditions. However, these polymer-based systems often have limited drug-loading capacity, suboptimal release kinetics, and/or promote adverse inflammatory responses. This manuscript investigates and describes a strategy for achieving controlled delivery of corticosteroids, based on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 70 publications
(80 reference statements)
0
22
0
Order By: Relevance
“…In comparison to (R)-DNCs-2, (S)-DNCs-2 had a much stronger interaction energy with levofloxacin, which generated efficient antimicrobial effects. This finding contributed to establishment of a controllable and sustained release formulation 51 55 .…”
Section: Resultsmentioning
confidence: 84%
“…In comparison to (R)-DNCs-2, (S)-DNCs-2 had a much stronger interaction energy with levofloxacin, which generated efficient antimicrobial effects. This finding contributed to establishment of a controllable and sustained release formulation 51 55 .…”
Section: Resultsmentioning
confidence: 84%
“…To verify this, we used DEX, as it is a lipophilic substance, 32 and synthetic glucocorticoid, as it is used clinically as an anti-inflammatory drug. 33 First, we quantified the drug loading amount on CTS and βCTS ENs. We confirmed that the βCTS ENs successfully loaded a larger amount of DEX compared to the bare CTS ENs, indicating a 2.3-fold increase in loading (data not shown).…”
Section: Resultsmentioning
confidence: 99%
“…As mentioned above, we anticipated that β-CD-grafted CTS ENs may have hydrophobic drug loading capacity. To verify this, we used DEX, as it is a lipophilic substance, and synthetic glucocorticoid, as it is used clinically as an anti-inflammatory drug . First, we quantified the drug loading amount on CTS and βCTS ENs.…”
Section: Resultsmentioning
confidence: 99%
“…In non-human primates and in rodents, the foreign body response was substantially delayed (for 6 and 15 months, respectively). Taken together, the data on dexamethasone dimer (Battiston et al 2021), GW2580 Farah et al 2019, paclitaxel , rapamycin (Farah et al 2013) and triamcinolone (Gursharan et al 2021) point out that crystalline drugs combine a high drug density with slow topical delivery through dissolution. Dissolution appears to occur at the surface of the crystals and thus obeys zero-order kinetics, i.e., initial-burst release (which is often encountered with bio-absorbable polymer coatings) can thus be avoided.…”
Section: Introductionmentioning
confidence: 99%